Place, Sport and Globalization: Making sense of the marca Barça - Shobe, Hunter (Treballs de la Societat Catalana de Geografia, 2008)
The case of Football Club (FC) Barcelona provides a compelling case forexamining the impact of globalization on the place/identity role of footballclubs. FC Barcelona has deep historical connections to Barcelona andCatalonia. These connections were de-emphasized by the clubs leadershipunder Josep Lluís Núñez (1978-2000) and Joan Gaspart (2000-2003) andpromoted again by Joan Laporta and his directors (elected in 2003). At thesame time, under Laporta, FC Barcelona has developed into a successfulglobal brand. How are we to understand this renewed focus on the local andnational discourses of place while the team is simultaneously promoted as aglobal brand? Although the local and global discourses seem to be at odds,the club leadership seamlessly promotes la marca Barça (the Barça Brand)while repoliticizing the club with an explicitly catalanista discourse. Theglobal and local discourses are not mutually exclusive. Rather, the local isdrawn upon in constructing the global discourse and the global is implicatedin the reproduction of the local (Massey, 1994, p.120).